Solid electrolyte and preparation method thereof and secondary battery
By using porous coordination polymer solid electrolytes with unsaturated metal sites in lithium-ion batteries, the problems of high chemical activity and safety hazards of metal negative electrodes are solved, and the battery performance with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202110222938.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-02-27
AI Technical Summary
The energy density of graphite-based negative electrodes in existing lithium-ion batteries is close to the ceiling, which cannot meet the needs of high endurance and standby. At the same time, the metal negative electrodes have high chemical activity, dendrite growth and safety hazards.
The porous coordination polymer with unsaturated metal sites is used as the matrix of the solid electrolyte. By coordinating the graft of anionic groups and cations, the rapid transmission of single cations is achieved, and the concentration polarization and dendritic growth are avoided.
It improves the electrochemical and safety performance of the battery, enhances the number of cation migrations, reduces the internal impedance, and significantly improves the cycle life and safety of the battery.
Smart Images

Figure CN114976227B_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of secondary batteries, and in particular to a solid electrolyte, a preparation method thereof, and a secondary battery. Background Art
[0002] With the development of economy and technology, most electronic industries (such as portable electronic devices, drones, electric vehicles, etc.) are in urgent need of energy storage devices with higher energy density, higher power density, longer cycle life and safer. However, the energy density of lithium-ion batteries based on graphite anodes is close to the ceiling and can no longer meet the endurance and standby requirements of users for the above devices. Metal anodes such as lithium, sodium, and potassium have high theoretical specific capacity and low electrochemical potential, which can greatly increase the energy density of secondary batteries and significantly improve user experience. However, metal anodes have problems such as high chemical activity (leading to low Coulomb efficiency), dendrite growth (causing side reactions and safety hazards) and large volume expansion (SEI film is constantly ruptured and rebuilt). The use of liquid electrolytes can easily cause safety hazards such as flammability and explosion, which hinders the commercialization of high energy density metal anode batteries.
[0003] In order to improve the problems existing in the above-mentioned metal negative electrodes, researchers replaced the liquid electrolyte with a solid electrolyte. Solid electrolytes mainly include polymer electrolytes, inorganic electrolytes (such as sulfur compound electrolytes, oxide electrolytes), and organic-inorganic composite electrolytes. Among them, polymer electrolytes have good processing performance, but low room temperature conductivity, low cation migration number, and are not resistant to oxidation; inorganic electrolytes have high ion conductivity, but are difficult to process and have poor electrode interface contact; organic-inorganic composite electrolytes can complement each other to a certain extent, but the existing organic-inorganic composite electrolytes still have problems such as low cation migration number, low ion conductivity, and poor composite uniformity, which cannot meet the improvement of the comprehensive performance of metal negative electrode batteries. Summary of the invention
[0004] In view of this, an embodiment of the present application provides a solid electrolyte that exhibits single cation conduction characteristics, can effectively avoid concentration polarization in the battery system, and inhibit the growth of metal negative electrode dendrites, thereby improving the electrochemical performance and safety performance of the battery.
[0005] Specifically, the first aspect of the embodiment of the present application provides a solid electrolyte, which includes a porous coordination polymer with unsaturated metal sites, anionic groups coordinated and grafted on the unsaturated metal sites, and cations combined with the anionic groups, wherein the anionic groups include one or more substituted carboxylate anionic groups and / or one or more substituted sulfonate anionic groups; the cations include one or more of lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions. By coordinating and fixing the anionic groups on the unsaturated metal sites of the porous coordination polymer, the solid electrolyte can achieve rapid transmission of single cations under poor solvent or even solvent-free conditions, with a high cation migration number, thereby avoiding concentration polarization caused by the movement of anions in the electrochemical system and reducing internal impedance; it can also effectively inhibit the growth of metal negative electrode dendrites, significantly improving the electrochemical performance and safety performance of the battery.
[0006] In the embodiment of the present application, the structural formula of the anionic group can be expressed as: -Y-R2-Z, wherein the Y represents an oxygen atom (O), a sulfur atom (S) or an imino group (-NH-), the R2 is a divalent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group, the Z is a carboxylate anion or a sulfonate anion, and the anionic group is coordinated with the unsaturated metal site through the Y. Y can form MO, MS, or MN coordination bonding with the metal atom of the unsaturated metal site, so that the anionic group is firmly bound to the porous coordination polymer.
[0007] In the embodiment of the present application, R2 is a hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group having 1 to 20 carbon atoms.
[0008] In some embodiments of the present application, R2 is any one of an alkylene group, a halogenated alkylene group, an alkyleneoxy group, a halogenated alkyleneoxy group, an alkenylene group, a halogenated alkenylene group, an alkenyleneoxy group, a halogenated alkenyleneoxy group, an arylene group, a halogenated arylene group, an aryleneoxy group, and a halogenated aryleneoxy group.
[0009] In the embodiment of the present application, the porous coordination polymer has M as the metal center and R-Xn as the organic ligand, wherein the M includes one or more metal elements of titanium, zirconium, hafnium, chromium, iron, cobalt, nickel, copper, and aluminum, and the metal element includes one or more valence states, and the R is an n-valent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbon group or a substituted hydrocarbon group, and n is an integer from 1 to 4, and the X is an oxygen-containing functional group that can form a metal-oxygen chemical bond with the unsaturated metal site. The porous coordination polymer has good film-forming properties, which can reduce the processing difficulty of the solid electrolyte, and has strong mechanical properties after film formation, which can improve the safety performance of the battery. The porous coordination polymer has a uniform porous structure, which is conducive to ion transport.
[0010] In the embodiment of the present application, X is a carboxyl group or a sulfonic acid group. Both the carboxyl group and the sulfonic acid group can form a MO bonding reaction with the unsaturated metal site of the porous coordination polymer.
[0011] In the embodiment of the present application, R is a hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group having 1 to 20 carbon atoms.
[0012] In the embodiment of the present application, R is any one of alkyl, alkylene, haloalkyl, haloalkylene, alkoxy, alkyleneoxy, haloalkoxy, haloalkyleneoxy, alkenyl, alkenylene, haloalkenyl, haloalkenylene, alkenoxy, alkenyleneoxy, haloalkenyloxy, haloalkenyleneoxy, aryl, arylene, halogenated aryl, halogenated arylene, aryloxy, aryleneoxy, halogenated aryloxy, and halogenated aryleneoxy.
[0013] In some embodiments of the present application, the organic ligand includes one or more of terephthalic acid, trimesic acid, biphenyl dicarboxylic acid, biphenyl tricarboxylic acid, and 1,3,5-tris(4-carboxyphenyl)benzene.
[0014] In the embodiment of the present application, the thickness of the solid electrolyte is 1 μm-100 μm. Suitable thickness can control the surface resistance and mechanical strength of the electrolyte layer at a suitable level, thereby improving battery performance.
[0015] In the embodiment of the present application, the solid electrolyte further comprises an electrolyte solvent, and the mass percentage of the electrolyte solvent in the solid electrolyte is less than or equal to 20%. The addition of a small amount of electrolyte solvent can further improve the ionic conductivity and improve the contact problem between the solid electrolyte and the electrode. The electrolyte solvent can be filled in the porous pore structure of the coordination polymer electrolyte.
[0016] In the embodiment of the present application, the solid electrolyte further comprises a binder. In the embodiment of the present application, the mass ratio of the coordination polymer electrolyte to the binder is between 1:1 and 100:1. The addition of an appropriate amount of binder can make the coordination polymer electrolyte form a better film, and can also form a tighter bond between the coordination polymer electrolytes, thereby improving the structural stability of the solid electrolyte membrane.
[0017] In an embodiment of the present application, the binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyimide, polybenzimidazole, polyethylene glycol, polyethylene oxide, polydopamine, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, polyvinyl pyrrolidone, polylactic acid, sodium alginate, poly(p-styrene sulfonic acid), lithium poly(p-styrene sulfonate) and gelatin.
[0018] A second aspect of an embodiment of the present application provides a method for preparing a solid electrolyte, comprising:
[0019] A coordination polymer electrolyte is made into a mixed slurry, the mixed slurry is coated into a film, and a solid electrolyte is obtained after drying; the coordination polymer electrolyte includes a porous coordination polymer with unsaturated metal sites, anionic groups coordinated and grafted on the unsaturated metal sites, and cations combined with the anionic groups, the anionic groups include one or more substituted carboxylate anionic groups and / or one or more substituted sulfonate anionic groups; the cations include one or more of lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions.
[0020] In the embodiment of the present application, the preparation of the coordination polymer electrolyte includes:
[0021] Dispersing the porous coordination polymer having unsaturated metal sites in a solution of a compound having an anionic group, stirring the reaction to coordinate and graft the compound having anionic groups onto the unsaturated metal sites to obtain a grafted product; the compound having anionic groups includes one or more of substituted carboxylic acids and substituted sulfonic acids;
[0022] The grafted product is placed in an electrolyte solution containing the salt of the cation, and stirred for reaction to obtain the coordination polymer electrolyte.
[0023] In the embodiment of the present application, before dispersing the porous coordination polymer having unsaturated metal sites in the compound solution having the anionic groups, an activation operation is also included. The activation operation can specifically be: activating the porous coordination polymer by vacuum heating at 80-350°C for 1-12 hours. The activation is beneficial to the subsequent coordination grafting reaction.
[0024] In an embodiment of the present application, the salt containing the cation includes one or more of hexafluorophosphate, hexafluoroarsenate, perchlorate, tetrafluoroborate, dioxalatoborate, difluorooxalatoborate, bisfluorosulfonyl imide salt, and bistrifluorosulfonyl imide salt containing the cation.
[0025] In the embodiment of the present application, the mixed slurry includes an organic solvent and / or a binder.
[0026] The method for preparing the solid electrolyte provided in the embodiment of the present application has a simple process, low preparation cost, low processing difficulty, and is suitable for large-scale production.
[0027] The embodiment of the present application also provides a secondary battery, including a positive electrode plate, a metal negative electrode plate and an electrolyte, wherein the electrolyte includes the solid electrolyte described in the first aspect of the embodiment of the present invention. The metal negative electrode plate can be a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode or an aluminum negative electrode. Accordingly, the secondary battery can be a lithium secondary battery, a sodium secondary battery, a potassium secondary battery, a magnesium secondary battery, a zinc secondary battery, and an aluminum secondary battery. The secondary battery has high cycle performance and high safety.
[0028] The embodiment of the present application also provides an electronic device, which includes a housing, and electronic components and batteries contained in the housing, wherein the batteries power the electronic components, and the batteries include the secondary batteries provided in the embodiment of the present application, and the secondary batteries are used to power the electronic device. The electronic device may be, but is not limited to, a mobile phone, a tablet computer, a smart wearable product, a drone, an electric car, and other electronic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A schematic diagram of the structure of a secondary battery provided in an embodiment of the present application;
[0030] Figure 2 It is a structural schematic diagram of an electronic device provided in an embodiment of the present application;
[0031] Figure 3 This is a scanning electron microscope (SEM) image of the solid electrolyte in Example 1 of the present application;
[0032] Figure 4 This is a scanning electron microscope image of the solid electrolyte in Example 2 of the present application;
[0033] Figure 5 This is a scanning electron microscope image of the solid electrolyte in Example 3 of the present application;
[0034] Figure 6 This is a scanning electron microscope image of the solid electrolyte in Example 4 of the present application;
[0035] Figure 7 This is a scanning electron microscope image of the solid electrolyte in Example 5 of the present application;
[0036] Figure 8 It is a cycle curve diagram of the batteries of Examples 1-7 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0037] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0038] See also Figure 1 , the embodiment of the present application provides a solid electrolyte 10, which can be used in a secondary battery, and the secondary battery includes a positive electrode plate 20, a metal negative electrode plate 30, and a solid electrolyte 10 arranged between the positive electrode plate 20 and the metal negative electrode plate 30. Among them, the solid electrolyte 10 includes a coordination polymer electrolyte, and the coordination polymer electrolyte includes a porous coordination polymer with an unsaturated metal site, an anion group coordinated and grafted on the unsaturated metal site, and a cation combined with the anion group. The anion group can be one or more of a substituted carboxylate anion group and a substituted sulfonate anion group; the cation is an electrolyte salt cation, and specifically can be one or more of lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions. The metal negative electrode plate 30 can be a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode, or an aluminum negative electrode. Accordingly, the secondary battery can be a lithium secondary battery, a sodium secondary battery, a potassium secondary battery, a magnesium secondary battery, a zinc secondary battery, or an aluminum secondary battery, and the secondary battery has high electrochemical performance and safety performance.
[0039] The solid electrolyte 10 of the embodiment of the present application, by grafting the anion group on the unsaturated metal site of the porous coordination polymer, because the anion is fixed by coordination, it can realize the rapid transmission of single cation under poor solvent or even solvent-free conditions, with a high cation migration number (greater than 0.85), so as to avoid the concentration polarization caused by the movement of anions in the electrochemical system, reduce the internal impedance; it can also effectively inhibit the growth of metal negative electrode dendrites, and significantly improve the electrochemical performance and safety performance of the battery. The use of the solid electrolyte of the embodiment of the present application can reduce or eliminate the use of electrolyte, reduce the direct contact between the electrolyte and the metal negative electrode, reduce side reactions, and improve the coulombic efficiency of the metal negative electrode. In addition, the solid electrolyte 10 of the embodiment of the present application has good interface contact with the electrode, and can load a small amount of solvent at the same time, further improve the ionic conductivity and improve the contact problem between the solid electrolyte and the electrode.
[0040] In the embodiment of the present application, the anion group may be one or more of a substituted carboxylate anion group and a substituted sulfonate anion group. The substituted carboxylate anion group may be an amino-substituted, hydroxy-substituted or thiol-substituted carboxylate anion group, and the substituted sulfonate anion group may be an amino-substituted, hydroxy-substituted or thiol-substituted sulfonate anion group.
[0041] In the embodiment of the present application, the structural formula of the anionic group can be expressed as: -Y-R2-Z, wherein Y represents an oxygen atom (O), a sulfur atom (S) or an imine group (-NH-), R2 is a divalent hydrocarbon group, a substituted hydrocarbon group, an oxyalkyl group or a substituted oxyalkyl group, and Z is a carboxylate anion (COO - ) or sulfonate anion (SO3- ), the anionic group is coordinated to the unsaturated metal site of the porous coordination polymer through Y. The structural formula of the substituted carboxylate anionic group is: -Y-R2-COO - , the structural formula of the substituted sulfonate anion group is: -Y-R2-SO3 - In some embodiments of the present application, when Z is a sulfonate anion, a greater degree of dissociation is more conducive to the increase of free cation concentration. In some embodiments of the present application, the anion group can be -O-R2-COO - 、-S-R2-COO - 、-NH-R2-COO - 、-O-R2-SO3 - 、-S-R2-SO3 - 、-NH-R2-SO3 - When the coordination polymer electrolyte molecular structure includes multiple anionic groups, the structures of the multiple anionic groups may be the same or different.
[0042] In some embodiments of the present application, R2 is a divalent hydrocarbon group, a substituted hydrocarbon group, an alkoxy group or a substituted alkoxy group having a carbon number of 1-20. Specifically, the carbon number of R2 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. In some embodiments, R2 can be selected from any one of alkylene, halogenated alkylene, alkyleneoxy, halogenated alkyleneoxy, alkenylene, halogenated alkenylene, alkenyleneoxy, halogenated alkenyleneoxy, arylene, halogenated arylene, aryleneoxy, and halogenated aryleneoxy. Among them, the carbon number of alkylene, halogenated alkylene, alkyleneoxy, and halogenated alkyleneoxy can be 1-20, and further, the carbon number can be 1-8. The carbon number of alkenylene, halogenated alkenylene, alkenyleneoxy, and halogenated alkenyleneoxy can be 2-20, and further, the carbon number can be 2-8. The number of carbon atoms in the arylene group, halogenated arylene group, aryleneoxy group, and halogenated aryleneoxy group can be 6-20, and further, the number of carbon atoms can be 6-10. If the number of carbon atoms is small, the molecular volume is small, and it is easy to coordinate and graft with metal atoms. If the number of carbon atoms is too large, the molecular volume is large, the hindrance is large, and it is not easy to coordinate and graft with metal atoms. The halogen in the haloalkylene group, haloalkyleneoxy group, haloalkenylene group, haloalkenyleneoxy group, haloarylene group, and haloaryleneoxy group includes fluorine, chlorine, bromine, and iodine, and the halogenation can be fully halogenated or partially halogenated. R2 can be a straight chain or branched hydrocarbon group, a substituted hydrocarbon group, or a hydrocarbonoxy group. In some embodiments, the anionic group can be, for example, -NH-CH2-CH2-SO3 - 、-NH-CH2-CH2-CH2-SO3 - 、-S-CH2-CH2-SO3 -、-S-CH2-CH2-CH2-SO3 - 、-O-CH2-CH2-SO3 - , -O-CH2-CH2-CH2-SO3-, -NH-CF2-CF2-COO - , -NH-CF2-CF2-CF2-SO3-, -S-CF2-CF2-CF2-COO - 、-S-CF2-CF2-SO3 - 、-O-CF2-CF2-SO3 - 、-O-CF2-CF2-CF2-COO - .
[0043] In the embodiment of the present application, the coordination polymer electrolyte is a metal-organic coordination polymer single ion solid electrolyte. Among them, the porous coordination polymer (Porous Coordination Polymers, PCPs) has M as the metal center and RX as the n The porous coordination polymer has a regular porous pore structure. M can be one or more of metal titanium (Ti), zirconium (Zr), hafnium (Hf), chromium (Cr), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and aluminum (Al). R is an n-valent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group, or a substituted hydrocarbonoxy group. n can be 1, 2, 3, or 4. X is an oxygen-containing functional group that can form a metal-oxygen chemical bond with the unsaturated metal site of the porous coordination polymer. Specifically, X can be a carboxyl group or a sulfonic acid group.
[0044] In the embodiment of the present invention, the porous coordination polymer has an unsaturated metal site, which is a metal center with unsaturated valence and coordination ability. The porous coordination polymer may have one or more unsaturated metal sites.
[0045] In the embodiment of the present invention, the porous coordination polymer may include one or more organic ligands. When including multiple organic ligands, the multiple organic ligands may be the same organic ligand or different organic ligands. The porous coordination polymer may include only carboxyl groups or sulfonic acid groups, or may include both carboxyl groups and sulfonic acid groups.
[0046] In the embodiment of the present invention, R is a hydrocarbon group, a substituted hydrocarbon group, an alkoxy group, or a substituted alkoxy group having 1 to 20 carbon atoms. Specifically, R can be any one of an alkyl group, an alkylene group, a haloalkyl group, a haloalkylene group, an alkoxy group, an alkyleneoxy group, a haloalkoxy group, a haloalkyleneoxy group, an alkenyl group, an alkenylene group, a haloalkenyl group, a haloalkenylene group, an alkenyloxy group, an alkenyleneoxy group, a haloalkenyloxy group, a haloalkenyleneoxy group, an aryl group, an arylene group, a haloaryl group, a haloarylene group, an aryloxy group, an aryleneoxy group, a haloaryloxy group, and a haloaryleneoxy group. The number of carbon atoms of the alkyl group, the alkylene group, the haloalkyl group, the haloalkylene group, the alkoxy group, the alkyleneoxy group, the haloalkoxy group, and the haloalkyleneoxy group is 1 to 20, and further, the number of carbon atoms is 1 to 8. The number of carbon atoms of alkenyl, alkenylene, halogenated alkenyl, halogenated alkenylene, alkenyloxy, alkenyleneoxy, halogenated alkenyloxy, and halogenated alkenyleneoxy is 2-20, and further, the number of carbon atoms is 2-8. The number of carbon atoms of aryl, arylene, halogenated aryl, halogenated arylene, aryloxy, aryleneoxy, halogenated aryloxy, and halogenated aryleneoxy is 6-20, and further, the number of carbon atoms is 6-10. The halogen in haloalkyl, haloalkylene, haloalkoxy, haloalkyleneoxy, haloalkenyl, haloalkenylene, haloalkenyloxy, haloalkenyleneoxy, halogenated aryl, halogenated arylene, halogenated aryloxy, and halogenated aryleneoxy includes fluorine, chlorine, bromine, or iodine. The halo may be fully halogenated or partially halogenated. R may be a straight or branched hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group, or a substituted hydrocarbonoxy group.
[0047] In some specific embodiments of the present application, the organic ligand includes one or more of terephthalic acid, trimesic acid, biphenyl dicarboxylic acid, biphenyl tricarboxylic acid, and 1,3,5-tris(4-carboxyphenyl)benzene.
[0048] In one embodiment of the present application, the structural formula of the coordination polymer electrolyte may be as shown in formula (1):
[0049]
[0050] In formula (1), M is a metal center, R can be a divalent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group, and specifically can be any one of an alkylene group, a halogenated alkylene group, an alkyleneoxy group, a halogenated alkyleneoxy group, an alkenylene group, a halogenated alkenylene group, an alkenyleneoxy group, a halogenated alkenyleneoxy group, an arylene group, a halogenated arylene group, an aryleneoxy group, and a halogenated aryleneoxy group. X1 is -COO - or -SO3 - Y is selected from O, S or NH, R2 is a divalent hydrocarbon group, a substituted hydrocarbon group, an oxyalkyl group or a substituted oxyalkyl group. Z is a carboxylate anion (COO - ) or sulfonate anion (SO3 -). A is a cation, which can be one or more of lithium ion, sodium ion, potassium ion, magnesium ion, zinc ion, and aluminum ion. n represents the degree of polymerization, which can be an integer greater than or equal to 1.
[0051] In the embodiment of the present application, the thickness of the solid electrolyte 10 can be designed according to actual needs, and the thickness of the solid electrolyte 10 can be 1μm-100μm. In some embodiments, the thickness of the solid electrolyte 10 can be 5μm-60μm, specifically 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 60μm. If the thickness of the solid electrolyte 10 is too thick, the surface resistance of the electrolyte layer is too large, which affects the battery performance. If the thickness is too thin, the mechanical strength is poor and it is easy to cause a short circuit.
[0052] In some embodiments of the present application, in order to further improve the ionic conductivity of the solid electrolyte 10 and improve the contact problem between the solid electrolyte 10 and the positive and negative electrodes, the solid electrolyte 10 may also include an electrolyte solvent, and the electrolyte solvent is filled in the micropores of the coordination polymer electrolyte, and the mass percentage of the electrolyte solvent in the solid electrolyte is less than or equal to 20%. In some embodiments, the mass percentage of the electrolyte solvent in the solid electrolyte is 1%-15%. In other embodiments, the mass percentage of the electrolyte solvent in the solid electrolyte is 3%-10%. In some other embodiments, the mass percentage of the electrolyte solvent in the solid electrolyte is 5%-8%. The electrolyte solvent can be one or more of a carbonate solvent, an ether solvent, and a carboxylate solvent. The electrolyte solvent can be a mixture of the above three solvents in any proportion. Among them, carbonate solvents include cyclic carbonates or chain carbonates. Cyclic carbonates can be one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), butylene carbonate (BC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC); chain carbonates can be one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). Ether solvents include cyclic ethers or chain ethers. Cyclic ethers can be one or more of 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ethers, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); chain ethers can be one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), and diethylene glycol dimethyl ether (TEGDME). The carboxylate solvent may specifically be one or more of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.
[0053] In some embodiments of the present application, the solid electrolyte also includes a binder. Since the coordination polymer electrolyte in the solid electrolyte of the present application embodiment is mostly a powder sample, the coordination polymer electrolyte can be better film-formed by adding a binder, and a tighter combination can be formed between the coordination polymer electrolytes to improve the structural stability of the solid electrolyte membrane. The binder can be one or more including polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), polyimide (PI), polybenzimidazole (PBI), polyethylene glycol (PEG), polyethylene oxide (PEO), polydopamine (PDA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyacrylic acid (PAA), lithium polyacrylate (LiPAA), polyvinyl pyrrolidone (PVP), polylactic acid (PLA), sodium alginate (SA), polystyrene sulfonic acid (PSS), lithium polystyrene sulfonate (LiPSS) and gelatin. In some embodiments of the present application, in the solid electrolyte 10, the mass ratio of the coordination polymer electrolyte to the binder can be 1-100: 1. Further, the mass ratio of the two can be 5-90: 1, or 10-80: 1, 20-60: 1, or 30-50: 1. Excessive binder content will reduce ionic conductivity and affect electrolyte ion transport. Under the condition of meeting the film formation requirements, controlling the binder content to a relatively small level is beneficial to improving the ion transport performance of the solid electrolyte.
[0054] The solid electrolyte 10 of the embodiment of the present application has a high cation (such as lithium ion, etc.) migration number, which can realize the rapid transmission of single cations, and the cation migration number is greater than 0.85. In some embodiments, the cation migration number is ≥0.9. The room temperature conductivity of the solid electrolyte 10 of the embodiment of the present application without electrolyte solvent is 0.5S / cm-5S / cm; the room temperature conductivity containing electrolyte solvent is 3S / cm-8S / cm.
[0055] In the embodiment of the present application, the metal negative electrode plate 30 may be a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode or an aluminum negative electrode. The lithium negative electrode, the sodium negative electrode, the potassium negative electrode, the magnesium negative electrode, the zinc negative electrode, and the aluminum negative electrode may be lithium, sodium, potassium, magnesium, zinc, aluminum metal single substances or their alloys, or the above metals or their alloys with a current collector. Taking the lithium negative electrode as an example, the lithium negative electrode may be a simple metallic lithium or a lithium alloy, or a metallic lithium or a lithium alloy including a current collector and disposed on the current collector. The lithium alloy may include at least one of a lithium silicon alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.
[0056] The present application also provides a method for preparing the solid electrolyte, comprising:
[0057] The coordination polymer electrolyte is made into a mixed slurry, the mixed slurry is coated into a film, and after drying, it is rolled into a certain thickness to obtain a solid electrolyte.
[0058] The mixed slurry may include a binder and an organic solvent. Specifically, the preparation process of the mixed slurry may be: the binder is dispersed in an organic solvent to obtain a mixed solution, and then the coordination polymer is dispersed in the mixed solution to obtain a mixed slurry. The organic solvent may be one or more of nitrogen methyl pyrrolidone (NMP), acetone, acetonitrile, methanol, ethanol, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, tetrahydrofuran, N,N-dimethylformamide (DMF), dimethyl ether, dimethyl sulfide, 1,3-dioxolane, 1,4-dioxolane, 1,2-dimethoxyethane, ethylene glycol dimethyl ether, bis-trifluoroethyl ether, hexafluoroisopropyl methyl ether, hexafluoroisopropyl ethyl ether, perfluorobutyl methyl ether, perfluorobutyl ethyl ether, tetrafluoroethyl tetrafluoropropyl ether, and tetrafluoroethyl octafluoropentyl ether.
[0059] In the embodiment of the present application, the preparation process of the coordination polymer electrolyte may include:
[0060] Step (1): activating a porous coordination polymer having unsaturated metal sites and dispersing the polymer in a solution of a compound having the above-mentioned anionic groups, stirring the reaction to coordinate and graft the compound having the anionic groups onto the unsaturated metal sites to obtain a grafted product; the compound having the anionic groups includes one or more of substituted carboxylic acids and substituted sulfonic acids;
[0061] Step (2): After the grafted product is dried, it is placed in an electrolyte solution containing a cation salt and stirred to react to obtain a coordination polymer electrolyte.
[0062] In the embodiment of the present application, in step (1), the operation of activating the porous coordination polymer can be specifically: activating the porous coordination polymer by vacuum heating at 80-350°C for 1-12 hours, and the activation is conducive to the subsequent coordination grafting reaction. In some embodiments, the compound having anionic groups can be HO-R2-COOH, HS-R2-COOH, NH2-R2-COOH, HO-R2-SO3H, HS-R2-SO3H, NH2-R2-SO3H. The stirring reaction time can be 6 hours to 48 hours. In the solution of the compound having anionic groups, the solvent can be one or more of nitrogen methyl pyrrolidone, acetone, acetonitrile, methanol, ethanol, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, tetrahydrofuran, N,N-dimethylformamide, dimethyl ether, dimethyl sulfide, 1,3-dioxolane, 1,4-dioxolane, 1,2-dimethoxyethane, ethylene glycol dimethyl ether, bis-trifluoroethyl ether, hexafluoroisopropyl methyl ether, hexafluoroisopropyl ethyl ether, perfluorobutyl methyl ether, perfluorobutyl ethyl ether, tetrafluoroethyl tetrafluoropropyl ether, and tetrafluoroethyl octafluoropentyl ether.
[0063] The porous coordination polymer with unsaturated metal sites in step (1) can be prepared by a solvothermal method, specifically, the organic ligand and the metal salt in a molar ratio of 1:(1-4) are dispersed in a solvent, ultrasonically dispersed and stirred for 10-60 minutes to obtain a mixed solution, and the mixed solution is placed in a reactor for a solvothermal reaction at 80-350° C. The metal salt is a salt including a metal center. The solvent in the solvent thermal reaction system includes, but is not limited to, one or more of deionized water, nitrogen methyl pyrrolidone, acetone, acetonitrile, methanol, ethanol, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, tetrahydrofuran, N,N-dimethylformamide, dimethyl ether, dimethyl sulfide, 1,3-dioxolane, 1,4-dioxolane, 1,2-dimethoxyethane, ethylene glycol dimethyl ether, bis-trifluoroethyl ether, hexafluoroisopropyl methyl ether, hexafluoroisopropyl ethyl ether, perfluorobutyl methyl ether, perfluorobutyl ethyl ether, tetrafluoroethyl tetrafluoropropyl ether, and tetrafluoroethyl octafluoropentyl ether. During the reaction, a regulator, such as formic acid, can also be added to adjust the product particle size, the number of defect sites, etc.
[0064] In step (2), in the electrolyte containing a salt of a cation, the salt containing a cation may be one or more of hexafluorophosphate, hexafluoroarsenate, perchlorate, tetrafluoroborate, dioxalate borate, difluorooxalate borate, bisfluorosulfonyl imide salt, and bistrifluorosulfonyl imide salt containing the above cations. For example, the salt containing a cation may be lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium bisfluorosulfonyl imide, and lithium bistrifluorosulfonyl imide. The organic solvent may be the above electrolyte solvent, such as a carbonate solvent, an ether solvent, or a carboxylate solvent; or it may be other organic solvents in the solvent described in step (1), such as acetonitrile. The stirring reaction time may be 6 to 48 hours. During the stirring reaction, the cation in the salt containing a cation undergoes ion exchange with the anion group. After the stirring reaction is completed, the coordination polymer electrolyte powder sample may be obtained by drying at 60-100°C. In the embodiment of the present application, when the solvent used in the electrolyte containing the salt of the cation is a commonly used electrolyte solvent, if the final solid electrolyte needs to contain a certain amount of electrolyte solvent, it is not necessary to completely dry it, so that the electrolyte solvent is partially retained. When the solvent used in the electrolyte containing the salt of the cation is not a commonly used electrolyte solvent, that is, other organic solvents, if the final solid electrolyte needs to contain a certain amount of electrolyte solvent, it needs to be completely dried before adding an appropriate amount of electrolyte solvent.
[0065] In a specific embodiment of the present application, the preparation process of the solid electrolyte includes: dispersing an organic ligand and a metal salt in a molar ratio of 1:1-4 in a solvent, ultrasonically dispersing and stirring for 10-60 minutes, placing the mixed solution in a reactor at 80-350°C for solvent thermal reaction, washing the product obtained by the reaction, and vacuum heating at 80-350°C for 1-12 hours to activate the powder sample. The powder sample after heating and activation is then dispersed in a compound solution with an anionic group and stirred for 6-48 hours, and the compound with anionic group is coordinated and grafted on the unsaturated metal site, and the grafted sample is collected after the reaction is completed. Then the dried grafted sample is placed in an electrolyte containing a cation salt and stirred for 6-48 hours for ion exchange, and then dried at 60-100°C to obtain a coordination polymer electrolyte powder sample, and then the coordination polymer electrolyte powder sample is dispersed in an organic solvent containing a binder, and scraped into an electrolyte membrane, and finally the electrolyte membrane is rolled to the target thickness.
[0066] The preparation method of the solid electrolyte in the embodiment of the present application is simple, the raw materials are easily available, and it can be prepared on a large scale.
[0067] like Figure 2As shown, an embodiment of the present application further provides an electronic device 200, which may be a mobile phone, a tablet computer, a smart wearable product, a drone, an electric car or other electronic product. The electronic device 200 includes a housing 201, and electronic components and a battery (not shown in the figure) located inside the housing 201, wherein the battery is the secondary battery provided in the embodiment of the present application above, the housing 201 may include a display screen assembled on the front side of the electronic device and a back cover assembled on the back side, and the battery may be fixed on the inside of the back cover to power the electronic components in the electronic device 200.
[0068] Taking lithium metal batteries as an example, the embodiments of the present application are further described in multiple embodiments.
[0069] Example 1
[0070] A solid electrolyte comprising an organic-inorganic coordination polymer (as shown in formula A) of MIL-100 (Al)-2-aminoethanesulfonic acid lithium with unsaturated aluminum sites and its application in lithium metal batteries.
[0071]
[0072] Preparation of solid electrolyte:
[0073] (1) 2.84 g aluminum nitrate nonahydrate and 1.04 g trimesic acid were dispersed in 40 mL 90% ethanol solution, ultrasonically dispersed and stirred for 30 minutes, and then the mixed solution was transferred to a reactor, heated to 120°C and kept warm for 1 hour. Subsequently, the sample was dried at 80°C, washed with ethanol three times, and activated by heating at 150°C in vacuum for 2 hours;
[0074] (2) The activated sample was then added to a 0.5 mol / L aqueous solution of 2-aminoethanesulfonic acid and stirred for 12 hours. The grafted product was then collected by centrifugation and washed with water and anhydrous ethanol. The obtained powder was dried in vacuum (150° C.) for 3 hours.
[0075] (3) soaking the product obtained in step (2) in a 1 mol / L acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) for 1 day, and drying in vacuum at 80° C. for 12 h after sufficient ion exchange to obtain a coordination polymer electrolyte;
[0076] (4) Use a binder to compound the coordination polymer electrolyte, such as polybenzimidazole (PBI). Specifically, 1g of PBI was dissolved in 10mL of N-methylpyrrolidone (NMP), stirred at 50°C for 24h, and then 4g of the above coordination polymer electrolyte sample was added and stirred for 12h to obtain a mixed slurry. The mixed slurry was then scraped onto a quartz plate, vacuum dried at 80°C overnight, and rolled to a certain thickness to obtain a slurry such as Figure 3The thickness of the solid electrolyte shown is 30 μm.
[0077] Preparation of LiCoO2 / Li lithium metal battery: Weigh 2% polyvinylidene fluoride (PVDF), 2% conductive agent super P and 96% lithium cobalt oxide (LiCoO2) by weight, add them into N-methylpyrrolidone (NMP) in sequence, stir and mix them evenly, coat the slurry on the aluminum foil current collector, dry, cold press and cut to obtain the positive electrode sheet.
[0078] The positive electrode sheet prepared above, the metal lithium negative electrode and the solid electrolyte prepared in Example 1 were assembled into a button cell.
[0079] Example 2
[0080] A solid electrolyte comprising an organic-inorganic coordination polymer (as shown in formula B) of MIL-100 (Al)-3-aminopropane sulfonate lithium with unsaturated aluminum sites and its application in lithium metal batteries.
[0081]
[0082] Preparation of solid electrolyte: 2.3g aluminum nitrate nonahydrate, 1.0g benzenetricarboxylic acid and 8mL nitric acid were dispersed in 50mL deionized water, ultrasonically dispersed and stirred for 20 minutes, and then the mixed solution was transferred to the reactor, heated to 210℃ and kept warm for 3 hours. Then the sample was cooled to room temperature, centrifuged and washed three times with deionized water and ethanol respectively, and activated by heating at 150℃ for 3 hours. The activated sample was then placed in an aqueous solution of 0.5mol / L 3-aminopropanesulfonic acid and stirred for 12h, then centrifuged and washed with water and anhydrous ethanol, and the obtained powder was vacuum dried (150℃) for 3h. Then it was immersed in an acetonitrile solution of 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) for 1 day, and after sufficient ion exchange, it was vacuum dried at 80℃ for 12h to obtain a coordination polymer electrolyte. The sample was then composited with a polybenzimidazole (PBI) binder. 0.5 g PBI was dissolved in 5 mL N-methylpyrrolidone (NMP) and stirred at 50°C for 24 h. Then 2 g of the above sample was added to the solution and stirred for 12 h. The mixed solution was then scraped onto a quartz plate and dried overnight at 80°C under vacuum. After being taken out, it was rolled to a certain thickness to obtain the following: Figure 4 The thickness of the solid electrolyte shown is 10 μm.
[0083] Preparation of LiCoO2 / Li battery: Assemble the positive electrode sheet prepared in Example 1, the metallic lithium negative electrode and the solid electrolyte prepared in Example 2 into a button battery.
[0084] Example 3
[0085] A solid electrolyte comprising an organic-inorganic coordination polymer (as shown in formula C) of MOF-808 (Zr)-2-aminoethanesulfonic acid lithium with unsaturated zirconium sites and its application in lithium metal batteries.
[0086]
[0087] Preparation of solid electrolyte: 9.7g of zirconium chloride octahydrate and 2.1g of trimesic acid were dissolved in DMF / formic acid (300mL / 300mL), ultrasonically dispersed and stirred for 30 minutes, and then the mixed solution was transferred to a reactor, heated to 130°C and kept warm for 48 hours. Then the sample was cooled to room temperature, centrifuged and washed with DMF three times, and heated at 150°C in vacuum for 8 hours to activate the sample. The activated sample was then placed in an aqueous solution of 0.5mol / L 2-aminoethanesulfonic acid and stirred for 12h, then centrifuged and washed with water and anhydrous ethanol, and the obtained powder was vacuum dried (150°C) for 3h. Then it was immersed in an acetonitrile solution of 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) for 1 day, and after sufficient ion exchange, it was vacuum dried at 80°C for 12h to obtain a coordination polymer electrolyte. The sample was then compounded with a binder, such as polybenzimidazole (PBI). 0.5 g of PBI was dissolved in 5 mL of N-methylpyrrolidone (NMP) and stirred at 50°C for 24 h. Then 2 g of the above sample was added to the solution and stirred for 12 h. The mixed solution was then scraped onto a quartz plate and dried overnight at 80°C under vacuum. After being taken out, it was rolled to a certain thickness to obtain the following: Figure 5 The thickness of the solid electrolyte shown is 15 μm.
[0088] Preparation of LiCoO2 / Li battery: Assemble the positive electrode sheet prepared in the above Example 1, the metal lithium negative electrode and the solid electrolyte prepared in Example 3 into a button battery.
[0089] Example 4
[0090] A solid electrolyte comprising an organic-inorganic coordination polymer (as shown in formula D) of MOF-808 (Zr)-3-aminopropane sulfonate lithium with unsaturated zirconium sites and its application in lithium metal batteries.
[0091]
[0092] Preparation of solid electrolyte: 9.7g of zirconium chloride octahydrate and 2.1g of trimesic acid were dissolved in DMF / formic acid (300mL / 300mL), ultrasonically dispersed and stirred for 30 minutes, and then the mixed solution was transferred to a reactor, heated to 130°C and kept warm for 48 hours. Then the sample was cooled to room temperature, centrifuged and washed with DMF three times, and vacuum heated at 150°C for 8 hours to activate the sample. The activated sample was then placed in an aqueous solution of 0.5mol / L 3-aminopropane sulfonic acid and stirred for 12h, then centrifuged and washed with water and anhydrous ethanol, and the obtained powder was vacuum dried (150°C) for 3h. Then it was immersed in an acetonitrile solution of 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) for 1 day, and after sufficient ion exchange, it was vacuum dried at 80°C for 12h to obtain a coordination polymer electrolyte. The sample was then composited with a binder, such as polybenzimidazole (PBI). 0.5 g PBI was dissolved in 5 mL N-methylpyrrolidone (NMP) and stirred at 50°C for 24 h. Then 2 g of the above sample was added to the solution and stirred for 12 h. The mixed solution was then scraped onto a quartz plate and dried overnight under vacuum at 80°C. After being taken out, it was rolled to a certain thickness to obtain the following: Figure 6 The thickness of the solid electrolyte shown is 20 μm.
[0093] Preparation of LiCoO2 / Li battery: The positive electrode sheet prepared in the above Example 1, the metal lithium negative electrode and the solid electrolyte prepared in Example 4 are assembled into a button battery.
[0094] Example 5
[0095] A solid electrolyte comprising an organic-inorganic coordination polymer (as shown in formula E) of MOF-808 (Zr)-3-mercaptopropane sulfonate lithium having unsaturated zirconium sites and its application in lithium metal batteries.
[0096]
[0097] Preparation of solid electrolyte: 9.7g of zirconium chloride octahydrate and 2.1g of trimesic acid were dissolved in DMF / formic acid (300mL / 300mL), ultrasonically dispersed and stirred for 30 minutes, and then the mixed solution was transferred to a reactor, heated to 130°C and kept warm for 48 hours. Then the sample was cooled to room temperature, centrifuged and washed with DMF three times, and heated at 150°C in vacuum for 8 hours to activate the sample. The activated sample was then placed in an aqueous solution of 0.5mol / L 3-mercaptopropane sulfonic acid and stirred for 12h, then centrifuged and washed with water and anhydrous ethanol, and the obtained powder was vacuum dried (150°C) for 3h. Then it was immersed in an acetonitrile solution of 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) for 1 day, and after sufficient ion exchange, it was vacuum dried at 80°C for 12h to obtain a coordination polymer electrolyte. The sample was then compounded with a binder, such as polybenzimidazole (PBI). 1g PBI was dissolved in 10mL N-methylpyrrolidone (NMP) and stirred at 50℃ for 24h. Then 4g of the above sample was added to the solution and stirred for 12h. The mixed solution was then scraped onto a quartz plate and dried overnight under vacuum at 80℃. After being taken out, it was rolled to a certain thickness to obtain the following: Figure 7 The thickness of the solid electrolyte shown is 25 μm.
[0098] Preparation of LiCoO2 / Li battery: The positive electrode sheet prepared in the above Example 1, the metal lithium negative electrode and the solid electrolyte prepared in Example 5 are assembled into a button battery.
[0099] Example 6
[0100] A solid electrolyte comprising an organic-inorganic coordination polymer (as shown in Formula F) of MOF-808 (Zr)-2-hydroxyethyl sulfonate lithium having unsaturated zirconium sites and its application in lithium metal batteries.
[0101]
[0102] Preparation of solid electrolyte: 9.7g of zirconium chloride octahydrate and 2.1g of trimesic acid were dissolved in DMF / formic acid (300mL / 300mL), ultrasonically dispersed and stirred for 30 minutes, and then the mixed solution was transferred to a reactor, heated to 130°C and kept warm for 48 hours. Then the sample was cooled to room temperature, centrifuged and washed with DMF three times, and vacuum heated at 150°C for 8 hours to activate the sample. The activated sample was then placed in an aqueous solution of 0.5mol / L 2-hydroxyethanesulfonic acid and stirred for 12h, then centrifuged and washed with water and anhydrous ethanol, and the obtained powder was vacuum dried (150°C) for 3h. Then it was immersed in an acetonitrile solution of 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) for 1 day, and after sufficient ion exchange, it was vacuum dried at 80°C for 12h to obtain a coordination polymer electrolyte. The sample was then compounded with a binder, such as polybenzimidazole (PBI). 1g PBI was dissolved in 10mL N-methylpyrrolidone (NMP) and stirred at 50℃ for 24h. Then 4g of the above sample was added to the solution and stirred for 12h. The mixed solution was then scraped onto a quartz plate, vacuum dried at 80℃ overnight, and rolled into a solid electrolyte with a thickness of 25μm.
[0103] Preparation of LiCoO2 / Li battery: The positive electrode sheet prepared in the above Example 1, the metal lithium negative electrode and the solid electrolyte prepared in Example 6 are assembled into a button battery.
[0104] Example 7 A solid electrolyte comprising an organic-inorganic coordination polymer of MOF-808 (Zr)-3-mercaptopropionic acid lithium (as shown in Formula G) having unsaturated zirconium sites and its application in lithium metal batteries.
[0105]
[0106] Preparation of solid electrolyte: 9.7g of zirconium chloride octahydrate and 2.1g of trimesic acid were dissolved in DMF / formic acid (300mL / 300mL), ultrasonically dispersed and stirred for 30 minutes, and then the mixed solution was transferred to a reactor, heated to 130°C and kept warm for 48 hours. Then the sample was cooled to room temperature, centrifuged and washed with DMF three times, and vacuum heated at 150°C for 8 hours to activate the sample. The activated sample was then placed in an aqueous solution of 0.5mol / L 3-mercaptopropionic acid and stirred for 12h, then centrifuged and washed with water and anhydrous ethanol, and the obtained powder was vacuum dried (150°C) for 3h. Then it was immersed in an acetonitrile solution of 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) for 1 day, and after sufficient ion exchange, it was vacuum dried at 80°C for 12h to obtain a coordination polymer electrolyte. The sample was then compounded with a binder, such as polybenzimidazole (PBI). 1g PBI was dissolved in 10mL N-methylpyrrolidone (NMP) and stirred at 50°C for 24h. Then 4g of the above sample was added to the solution and stirred for 12h. The mixed solution was then scraped onto a quartz plate, vacuum dried at 80°C overnight, and rolled into a solid electrolyte with a thickness of 20μm.
[0107] Preparation of LiCoO2 / Li battery: The positive electrode sheet prepared in the above Example 1, the metal lithium negative electrode and the solid electrolyte prepared in Example 7 are assembled into a button battery.
[0108] Comparative Example 1
[0109] Preparation of LiCoO2 / Li battery: Assemble the metal lithium negative electrode, the positive electrode prepared in Example 1 and the PE separator into a button battery, and add 50 μL of 1.0 mol / L LiPF6 electrolyte (EC, DEC, FEC weight ratio is 47:47:6).
[0110] Comparative Example 2
[0111] Preparation of LiCoO2 / Li battery: The metal lithium negative electrode, the positive electrode prepared in Example 1 and the 50 μm oxide ceramic electrolyte (Li7La3Zr2O 12 , LLZO) are assembled into button batteries.
[0112] In order to strongly support the beneficial effects brought about by the technical solutions of Examples 1-7 of the present application, the following tests are provided.
[0113] LiCoO2 / Li battery cycle performance test: The batteries prepared in Examples 1-7 and Comparative Examples 1-2 were subjected to charge and discharge tests according to a 0.2C / 0.5C charge and discharge regime, with a voltage range of 3.0-4.5V. The test results are shown in Tables 1 and Figure 8 shown.
[0114] LiCoO2 / Li battery rate performance test: The batteries prepared in Examples 1-7 and Comparative Examples 1-2 were subjected to charge and discharge tests at charge and discharge rates of 0.2 / 0.2C, 0.2 / 0.5C, 0.2 / 1.0C, 0.2 / 1.5C and 0.2 / 2.0C, with a voltage range of 3.0-4.5V. The capacity retention rate at 2.0C relative to 0.2C was recorded. The test results are shown in Table 1.
[0115] Table 1 Test results of different battery performance
[0116]
[0117] From the results in Table 1, it can be seen that the capacity retention rate of the lithium cobalt oxide / lithium battery in Examples 1-7 of the present application after 50 cycles is higher than the capacity retention rate of the lithium cobalt oxide / lithium battery in Comparative Examples 1-2 after 50 cycles. Figure 8 It can be seen from the test results that the capacity retention rate of the lithium cobalt oxide / lithium battery in Examples 1-7 of the present application after 100 cycles is higher than the capacity retention rate of the lithium cobalt oxide / lithium battery in Comparative Example 1-2 after 100 cycles. This shows that the use of the metal-organic coordination polymer single-ion solid electrolyte in the embodiments of the present application can significantly improve the cycle performance of the battery. In addition, it can be seen from Table 1 that the lithium ion migration number of the solid electrolyte in Examples 1-7 of the present application is greater than or equal to 0.9, which is much higher than the lithium ion migration number of the liquid electrolyte in Comparative Example 1. This is because the solid electrolyte used in the batteries of Examples 1-7 of the present application can realize single cation transport and has a high cation migration number. By realizing single ion transport, the generation of concentration polarization in the battery system can be effectively avoided, the deposition / dissolution behavior of lithium ions at the lithium negative electrode can be adjusted, the growth of lithium negative electrode dendrites can be inhibited, and the battery cycle performance can be improved.
[0118] Compared with Comparative Example 2, the lithium cobalt oxide / lithium batteries in Examples 1-7 of the present application show better cycle performance, mainly because the solid electrolytes in Examples 1-7 of the present application have good interface contact with the electrodes, which can reduce the interface impedance and improve the battery cycle stability. At the same time, the rate performance of the lithium cobalt oxide / lithium batteries in Examples 1-7 of the present application is similar to that of the liquid electrolyte battery in Comparative Example 1, and is better than the oxide ceramic solid electrolyte battery in Comparative Example 2.
Claims
1. A solid electrolyte, characterized in that The solid electrolyte includes a porous coordination polymer with unsaturated metal sites, anionic groups coordinated and grafted on the unsaturated metal sites, and cations combined with the anionic groups, wherein the anionic groups include one or more substituted carboxylate anionic groups and / or one or more substituted sulfonate anionic groups; the structural formula of the anionic group is: -Y-R2-Z, wherein Y represents an oxygen atom, a sulfur atom or an imine group, R2 is a divalent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group, Z is a carboxylate anion or a sulfonate anion, and the anionic group is coordinated with the unsaturated metal site through Y; the cations include one or more of lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions.
2. The solid electrolyte according to claim 1, characterized in that The R2 is a hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group having 1 to 20 carbon atoms.
3. The solid electrolyte according to claim 1 or 2, characterized in that The R2 is any one of an alkylene group, a halogenated alkylene group, an alkyleneoxy group, a halogenated alkyleneoxy group, an alkenylene group, a halogenated alkenylene group, an alkenyleneoxy group, a halogenated alkenyleneoxy group, an arylene group, a halogenated arylene group, an aryleneoxy group, and a halogenated aryleneoxy group.
4. The solid electrolyte according to any one of claims 1 to 3, characterized in that The porous coordination polymer comprises a metal center and an organic ligand, wherein the metal center comprises one or more metal elements selected from titanium, zirconium, hafnium, chromium, iron, cobalt, nickel, copper and aluminum, wherein the metal element comprises one or more valence states, and the organic ligand is RX n , wherein R is an n-valent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group, n is an integer from 1 to 4, and X is an oxygen-containing functional group that forms a metal-oxygen chemical bond with the unsaturated metal site.
5. The solid electrolyte according to claim 4, characterized in that The X is a carboxyl group or a sulfonic acid group.
6. The solid electrolyte according to claim 4 or 5, characterized in that The R is a hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group having 1 to 20 carbon atoms.
7. The solid electrolyte according to any one of claims 4 to 6, characterized in that The R is any one of alkyl, alkylene, haloalkyl, haloalkylene, alkoxy, alkyleneoxy, haloalkoxy, haloalkyleneoxy, alkenyl, alkenylene, haloalkenyl, haloalkenylene, alkenoxy, alkenyleneoxy, haloalkenyloxy, haloalkenyleneoxy, aryl, arylene, halogenated aryl, halogenated arylene, aryloxy, aryleneoxy, halogenated aryloxy, and halogenated aryleneoxy.
8. The solid electrolyte according to any one of claims 4 to 7, characterized in that The organic ligand includes one or more of terephthalic acid, trimesic acid, biphenyl dicarboxylic acid, biphenyl tricarboxylic acid, and 1,3,5-tris(4-carboxyphenyl)benzene.
9. The solid electrolyte according to any one of claims 1 to 8, characterized in that The thickness of the solid electrolyte is 1 μm-100 μm.
10. The solid electrolyte according to any one of claims 1 to 9, characterized in that The solid electrolyte further includes an electrolyte solvent, and the mass percentage of the electrolyte solvent in the solid electrolyte is less than or equal to 20%.
11. The solid electrolyte according to any one of claims 1 to 10, characterized in that The solid electrolyte also includes a binder.
12. The solid electrolyte according to claim 11, characterized in that The binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyimide, polybenzimidazole, polyethylene glycol, polyethylene oxide, polydopamine, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, polyvinyl pyrrolidone, polylactic acid, sodium alginate, poly(p-styrene sulfonic acid), lithium poly(p-styrene sulfonate) and gelatin.
13. A method for preparing a solid electrolyte, characterized in that: include: The coordination polymer electrolyte is made into a mixed slurry, the mixed slurry is coated into a film, and a solid electrolyte is obtained after drying; The coordination polymer electrolyte includes a porous coordination polymer with unsaturated metal sites, anionic groups coordinated and grafted on the unsaturated metal sites, and cations combined with the anionic groups, wherein the anionic groups include one or more substituted carboxylate anionic groups and / or one or more substituted sulfonate anionic groups; the structural formula of the anionic group is: -Y-R2-Z, wherein Y represents an oxygen atom, a sulfur atom or an imine group, R2 is a divalent hydrocarbon group, a substituted hydrocarbon group, a hydrocarbonoxy group or a substituted hydrocarbonoxy group, Z is a carboxylate anion or a sulfonate anion, and the anionic group is coordinated with the unsaturated metal site through Y; the cations include one or more of lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions.
14. The preparation method according to claim 13, characterized in that: The preparation of the coordination polymer electrolyte comprises: Dispersing the porous coordination polymer having unsaturated metal sites in a solution of a compound having an anionic group, stirring the reaction to coordinate and graft the compound having anionic groups onto the unsaturated metal sites to obtain a grafted product; the compound having anionic groups includes one or more of substituted carboxylic acids and substituted sulfonic acids; The grafted product is placed in an electrolyte solution containing the salt of the cation, and stirred for reaction to obtain the coordination polymer electrolyte.
15. The preparation method according to claim 14, characterized in that: Before dispersing the porous coordination polymer having unsaturated metal sites in the compound solution having the anionic groups, the method further comprises: The porous coordination polymer having unsaturated metal sites is activated by heating at 80° C. to 350° C. in vacuum for 1 to 12 hours.
16. The preparation method according to claim 14, characterized in that: The salt containing the cation includes one or more of hexafluorophosphate, hexafluoroarsenate, perchlorate, tetrafluoroborate, dioxalate borate, difluorooxalate borate, bisfluorosulfonyl imide salt, and bistrifluorosulfonyl imide salt containing the cation.
17. The preparation method according to claim 13, characterized in that: The mixed slurry includes an organic solvent and / or a binder.
18. A secondary battery, characterized in that: It comprises a positive electrode plate, a metal negative electrode plate and an electrolyte, wherein the electrolyte comprises a solid electrolyte as described in any one of claims 1 to 12.
19. An electronic device, characterized in that: It comprises a shell, and electronic components and a battery housed in the shell, wherein the battery supplies power to the electronic components, and the battery comprises the secondary battery as claimed in claim 18.
Citation Information
Patent Citations
Solid-state electrolytes with biomimetic ionic channels for batteries and methods of making same
US20190288331A1
Cited By
Solid electrolyte and preparation method therefor, and secondary battery
WO2022179559A1